Four cases in sports competition policy: Baseball, judo, football, and motor racing - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2017)
Practices and conducts in professional and even amateur sports can be subject to competition laws as soon as commercial activities are involved. From an economic perspective, this implies that both directly commercial activities like the sale of broadcasting/media rights and indirectly commercial activities like defining and enforcing the rules of the games can be hit by competition policy interventions. Setting and enforcing the rules of the game is an activity with commercial effects because it influences attractiveness and marketability of the sports in question. After discussing fundamental issues, this contributions reviews selected landmark cases in sports competition policy from an economic perspective. This includes the U.S. baseball antitrust exemption, access rules to Judo tournaments, sale systems of media rights in European football as well as a unique combination of long-run exclusivity contracts, skewed allocation of common revenues, and special influences on rule-setting by some competitors in Formula One motor racing. Eventually, the areas of state aid to football clubs and mergers in Danish football are sketched.
Keywords: K21; L40; Z20; L83; L82; 330; sports economics; antitrust; competition policy; baseball; judo; football; soccer; motor racing; formula one; media rights; sports broadcasting; competitive balance; cartels; abuse of dominance